Risks and Opportunities Related to the Internal and External Context of Organizations - Alina MATUSZAK-FLEJSZMAN; Beata PALIWODA (Communications of International Proceedings, 2021)
Appropriate approach to risk management determine the effectiveness of organizations management as such. Risk management is implemented in different ways and in different areas of the business, including areas related to the internal factors and conditions (e.g. values, knowledge, performance, processes) and areas related to the external factors and conditions (e.g. legal issues, technological issues, competition, market). Organizations have different approach to dealing with significant risks (including involvement of top management, implementation of contingency plans or providing relevant training to staff regarding risk management). The objective of this paper is to verify in which areas of the business related to organizational internal and external context risks and opportunities are identified the most frequently and verify differences between organizations with implemented any of the standardized management system (such as ISO 9001, ISO 14001 or ISO 45001) and organizations without any such system. An analysis was carried out on the group of 123 organizations, operating in Poland among which 73 have implemented standardized management system and 50 do not operate under any standardized management system. Research contains analysis on the risks and opportunities management practices in surveyed organizations and internal and external areas where risks and opportunities have been identified. Results of the study indicates that the areas in which risks and opportunities are identified by two groups of researched organizations are similar, however organizations with implemented standardized systems, identifies risks and opportunities (both, those related to the internal context and those related to the external context) more often in each area.
Keywords: Risk-Based Thinking; Quality Management System; Environmental Management System; Occupational Health and Safety Management System; Context Of The Organization; Internal Context; External Context.